Strategic Collaboration as a Means of Mediation in Translating Culturally Ambiguous Text: A Case Study - Kim, Dae-jin (Meta, 2006)
AbstractThis paper attempts to explore the notion of mediation processes involved in strategic collaboration in translating culturally ambiguous texts. Data for analysis were gathered from on-line exchanges of opinions and comments accrued through the reciprocal translation processes between Korean and American translators. Analytic taxonomy to determine collaboration efforts was established and every exchange of transactions was analyzed in accordance with the taxonomy. The result of this study suggests that the translation of culturally ambiguous texts can be facilitated through highly mediated collaboration between two participants, one of whom is well versed in cultures of the source text (Korean) whereas the other partner is native speaker of the target text (English). Actual samples of transactions are presented with analysis on mediation and negotiation processes.